Baby Blues Syndrome as a Reason For Forgiveness in Criminal Law System For Mothers Who Abuse Their Babies After Giving Birth - Hidayat, Beni; Zulfiko, Riki (Fakultas Hukum Universitas Djuanda, 2025)
Baby blues syndrome has recently become a hot topic and a fact that often occurs in today's society. Becoming a mother of course makes women feel amazed when they see the child they have just given birth to, so mothers often feel enthusiastic about caring for their child, but some women actually feel the opposite. This cruel act cannot be separated from the hormonal changes that occur in mothers after giving birth, medical doctors call this condition Baby Blues Syndrome. because basically Baby Blues Syndrome is not only related to hormonal changes after giving birth, but is also related to the mother's mental health, especially if the mother commits a crime, such as a mother in Jember Regency, East Java, who was determined to throw her baby into a well until it died because of frequent bullying. Based on this case, it is necessary to explore more deeply regarding baby blues syndrome as a reason for forgiveness for mothers who abuse their children after giving birth. By using a normative research approach, namely a research method on statutory regulations both from the perspective of the hierarchy of legal regulations (vertical), as well as the harmonious relationship between legal regulations (horizontal).